Electrochemical oxidation of chloramphenicol by modified Sm-PEG-PbO2 anodes: Performance and mechanism. (June 2023) - Zhang, Chaoyang; Gao, Conghao; Yang, Shumin; He, Xin; Chen, Yue; Qin, Xiao; Tang, Yulin
Abstract: Chloramphenicol (CAP) is used extensively in industry and daily life, but its abuse has seriously affected the environment and public health. In this paper, a new composite PbO2 electrode was obtained through the modification Sm and polyethylene glycol (PEG), and an electrocatalytic oxidation technology of CAP degradation was investigated. The results showed that the catalytic degradation ability and industrial service life of the PEG-Sm-PbO2 composite electrode were significantly enhanced. Co-doping inhibited the growth of grains, resulting in the formation of refined pyramidal grains on the surface of the electrode, which increased the number of active spots. The industrial service life of the modified electrode was improved by 87.0%. In addition, the degradation effect under different conditions and mechanism of CAP were also explored. The optimal conditions for CAP degradation were explored, at which time the CAP degradation rate reached 99.1%. The degradation process was in accordance with the primary reaction kinetics, and the apparent rate constant of CAP at the PEG-Sm-PbO2 electrode was raised by 57.1% in comparison with the unmodified electrode, indicating that the modification facilitated the degradation of CAP in the electrode. Finally, two possible CAP degradation pathways were deduced. The results will provide technical support and a theoretical basis for the degradation of persistent organic pollutants. Graphical abstract: Image 1 Highlights: The PbO2 electrode was modified using Sm and PEG. Optimization of oxidation performance and lifetime of the PEG-Sm-PbO2 electrode. The PEG-Sm-PbO2 electrode is more effective in the degradation of CAP. The degradation pathway and mechanism of CAP were summarized.